Effect of surface finishing on friction and wear of Poly-Ether-Ether-Ketone (PEEK) under oil lubrication - Andrade,Thiago Fontoura de (2016)
Abstract The tribological properties of poly-ether-ether-ketone (PEEK) containing 30% of carbon fiber were studied in an oil-lubricated environment and different surface finishing of the metallic counterbody. Four different finishing processes, commonly used in the automotive industry, were chosen for this study: turning, grinding, honing and polishing. The test system used was tri-pin on disc with pins made of PEEK and counterbody made of steel; they were fully immersed in ATF Dexron VI oil. Some test parameters were held constant, such as the apparent pressure of 2 MPa, linear velocity of 2 m/s, oil temperature at 85 °C, and the time - 120 minutes. The lubrication regime for the apparent pressure of 1 MPa to 7 MPa range was also studied at different sliding speeds. A direct correlation was found between the wear rate, friction coefficient and the lubrication regime, wherein wear under hydrodynamic lubrication was, on average, approximately 5 times lower, and the friction coefficient 3 times lower than under boundary lubrication.